ANALISIS PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PT. Temprina Media Grafika Semarang) - Kusumah, Evi Teja; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2015)
Each company must be focuses on achieving its obejctive, to do that companies have to be flexible with the rapidly changing environment in order to survive in the market competition. The existence of human resources quality and competence has become a necessity for the company to have a better performance. According to some views,Â motivation, compensation, and organizational culture are believed to affect the performance of a company. However, in some studies, showed different results. Seeing the difference between the views and research results, as well as the gap between one research to other research, the authors intend to examine how far the relationship between motivation, organizational culture, and compensation affects the performance of employees.The data in this study were collected through questionnaires that implemented to 55 permanent lemployees of PT Temprina Media GrafikaÂ Semarang. The techniques of data analysis in this research includes the test of reliability, validity, classical assumptions, multiple regression, and Sobel test to examine the mediation effect.These results indicate that organizational culture have positive and significant effect on the motivation and performance, compensation have significant and positive effect on the motivation and performance, and motivation have positive and significant impact on performance. Additionally, motivation is proven as mediator relationship between organizational culture and compensation to performance.